Sub-acute cardiac magnetic resonance to predict irreversible reduction in left ventricular ejection fraction after ST-segment elevation myocardial infarction: A DANAMI-3 sub-study. (15th February 2020) - Alzuhairi, Karam Sadoon; Lønborg, Jacob; Ahtarovski, Kiril Aleksov; Nepper-Christensen, Lars; Kyhl, Kasper; Lassen, Jens F.; Sørensen, Rikke; Joshi, Francis; Ghotbi, Adam Ali; Schoos, Mikkel; Goransson, Christoffer; Bertelsen, Litten; et al.
Abstract: Aims: To predict irreversible reduction in left ventricular ejection fraction (LVEF) during admission for ST-segment elevation myocardial infarction (STEMI) using cardiac magnetic resonance (CMR) in addition to classical clinical parameters. Irreversible reduction in LVEF is an important prognostic factor after STEMI which necessitates medical therapy and implantation of prophylactic implantable cardioverter defibrillator (ICD). Methods and results: A post-hoc analysis of DANAMI-3 trial program (Third DANish Study of Optimal Acute Treatment of Patients With ST-elevation Myocardial Infarction) which recruited 649 patients who had CMR performed during index hospitalization and after 3 months. Patients were divided into two groups according to CMR-LVEF at 3 months: Group 1 with LVEF≤35% and Group 2 with LVEF>35%. Group 1 included 15 patients (2.3%) while Group 2 included 634 patients (97.7%). A multivariate analysis showed that: Killip class >1 (OR 7.39; CI:1.47–36.21, P = 0.01), symptom onset-to-wire ≥6 h (OR 7.19; CI 1.07–50.91, P = 0.04), LVEF≤35% using index echocardiography (OR 7.11; CI: 1.27–47.43, P = 0.03), and infarct size ≥40% of LV on index CMR (OR 42.62; CI:7.83–328.29, P < 0.001) independently correlated with a final LVEF≤35%. Clinical models consisted of these parameters could identify 7 out of 15 patients in Group 1 with 100% positive predictive value. Conclusion: Together with other clinical measurements, the assessment of infarct size using late Gadolinium enhancement by CMR during hospitalization is a strong predictor of irreversible reduction in CMR_LVEF ≤35. That could potentially, after validation with future research, aids the selection and treatment of high-risk patients after STEMI, including implantation of prophylactic ICD during index hospitalization. Highlights: Irreversible damage to the myocardium after STEMI can be predicted in 47% of the patients. ICD implantation can be considered in these patients with irreversible damage to the myocardium. Cardiac MRI during admission for STEMI can help directing the future treatment in selected patients. 77% of STEMI patients with LVEF <35% will experience increase in their LVEF to >35% within three months.